Covid-19 and Italian small and medium-sized enterprises: consequences, threats and opportunities. - Pencarelli, Tonino; Cesaroni, Francesca Maria; Demartini, Paola (Piccola Impresa / Small Business, 2021)
Abstract During this intense global pandemic, many small entrepreneurs risk going out of business due to the fall in demand and management constraints imposed by national governments that have obliged them to go into lockdown and follow public health protocols. However, we believe that the health emergency can also represent an opportunity for micro and SMEs to rethink their current business models and innovate them, identifying new market segments, new value propositions, new resources and new actors with whom to anticipate, realise and deliver value to consumers. In this editorial, the editors of the journal Piccola Impresa/Small Business propose some reflections on the consequences, threats and opportunities Covid-19 has brought about for the SME sector, focusing particularly on the Italian ones.